The elderly recognizing themselves as vulnerable to falls in the concreteness of the femoral fracture - Aparecido de Carvalho, Cesar Junior [UNESP]; Mangini Bocchi, Silvia Cristina [UNESP] (Assoc Brasileira Enfermagem, 2017)
Objectives: understand the experience of the elderly with falls followed by femoral fracture and elaborate theoretical model of this process of lived experience. Method: qualitative research with theoretical saturation through analysis of the ninth nondirected interview of elderly who underwent such experience. Interviews were recorded, transcribed, and analyzed according to Grounded Theory. Results: three categories emerged (sub-processes): evaluating signs and symptoms of fracture after the fall; feeling sad and insecure with the new condition; and finding oneself susceptible to fractures. From realignment of these categories (sub-processes) we could abstract the central category (process), recognizing oneself as vulnerable to falls in the concreteness of the fracture. Conclusion: the theoretical model considering the Symbolic Interactionism signals the implementation of continued program for fall prevention, with teaching strategies that encourage the elderly to reflect on the concreteness of contexts in which there is risk of occurring injury to their health.
Keywords: Elderly; Accidents by Falls; Fractures of Femur; Care; Vulnerability